Camk2a-Cre and Tshz3 Expression in Mouse Striatal Cholinergic Interneurons: Implications for Autism Spectrum Disorder - Caubit, Xavier; Arbeille, Elise; Chabbert, Dorian; Desprez, Florence; Messak, Imane; Fatmi, Ahmed; Habermann, Bianca; Gubellini, Paolo; Fasano, Laurent (Frontiers in Genetics, 2021)
Camk2a-Cre mice have been widely used to study the postnatal function of several genes in forebrain projection neurons, including cortical projection neurons (CPNs) and striatal medium-sized spiny neurons (MSNs). We linked heterozygous deletion of TSHZ3/Tshz3 gene to autism spectrum disorder (ASD) and used Camk2a-Cre mice to investigate the postnatal function of Tshz3, which is expressed by CPNs but not MSNs. Recently, single-cell transcriptomics of the adult mouse striatum revealed the expression of Camk2a in interneurons and showed Tshz3 expression in striatal cholinergic interneurons (SCINs), which are attracting increasing interest in the field of ASD. These data and the phenotypic similarity between the mice with Tshz3 haploinsufficiency and Camk2a-Cre-dependent conditional deletion of Tshz3 (Camk2a-cKO) prompted us to better characterize the expression of Tshz3 and the activity of Camk2a-Cre transgene in the striatum. Here, we show that the great majority of Tshz3-expressing cells are SCINs and that all SCINs express Tshz3. Using lineage tracing, we demonstrate that the Camk2a-Cre transgene is expressed in the SCIN lineage where it can efficiently elicit the deletion of the Tshz3-floxed allele. Moreover, transcriptomic and bioinformatic analysis in Camk2a-cKO mice showed dysregulated striatal expression of a number of genes, including genes whose human orthologues are associated with ASD and synaptic signaling. These findings identifying the expression of the Camk2a-Cre transgene in SCINs lineage lead to a reappraisal of the interpretation of experiments using Camk2a-Cre-dependent gene manipulations. They are also useful to decipher the cellular and molecular substrates of the ASD-related behavioral abnormalities observed in Tshz3 mouse models.